Evaluation of Sensitivity of Plasmodium vivax to Chloroquine - Nateghpour M; Sayedzadeh SA; Edrissian GhH; Raeisi A; Jahantigh A; Motevalli-Haghi A; Mohseni Gh; Rahimi A (Tehran University of Medical Sciences, 2007)
Background: To monitor the current response of P. vivax to chloroquine in South and Southeast Iran. Methods: The study was undertaken from August 2004 until August 2005 at the Bandar- Abbas, Iranshahr, Nikshahr and Chabahar districts. A total of 195 patients out of 225 parasitologically positive P. vivax cases completed the study .The patients were given a standard 3- day regimen of chloroquine and followed-up clinically and parasitologically according to the world Health Organization guideline with some modifications. Results of study were addressed as mean of parasite clearance time (MPCT). Results: The patients responded to the regimen of chloroquine within 24-120 hours. The MPCTs of P. vivax for Bandar- Abbas, Iranshahr, Nikshahr and Chabahar districts were 63.05(±15.37), 56(± 21.7), 70.92 (±6.51) and 58(±14) hours, respectively and for the whole study area (South and South East of Iran) was 63.50(±15.84) hours. The results of the whole studied areas indicate that difference of MPCT between male and female patients is marginally significant (P=0.05). Conclusion: Although, parasite clearance time for a number of cases occurred within 96 and 120 hours, no P. vivax parasites had reappeared in considered patients after day five within 28 days follow- up, reflecting that chloroquine is still an efficacious drug for the treatment of vivax malaria in the studied districts. Higher MPCT in Nikshahr district than the other districts indicating this could be an early sign for reduced susceptibility of the parasite to the drug.